TVET Graduates Employability for Construction Industry: A Mixed-Method Study - Auta, Mohammed Adamu; M. Onwusuru, Ijeoma (Online Journal for TVET Practitioners, 2022)
Studies conducted in the past indicated that, there exist a gap between what the industries want and what the respective institutions especially TVET institutions of higher learning produced due to near absence of employability skills. This is a report on the study of employability skills that TVET graduate aspiring to work in the construction industry should acquire. The study adopted mixed-methods design and the participants comprises of 439 construction industry practitioner with varying roles and years of experience. Questionnaire and interviews were used to collect data, while mean, standard deviation was used to analyze the quantitative data. Thematic analysis was used to analyze the qualitative data. The findings of the study indicated that, personal qualities, teamwork skills, communication skills, problem solving skills, leadership skills, informational skills and technological skills were identified as the essential skills needed in the construction industry.